Does European Unemployment Prop Up American Wages? National Labor Markets and Global Trade: Comment - Meckl, Jürgen (American Economic Review, 2006)
Does European Unemployment Prop Up American Wages? National Labor Markets and Global Trade: Comment by Jürgen Meckl. Published in volume 96, issue 5, pages 1924-1930 of American Economic Review, December 2006